Comparison of epidural versus spinal anesthesia methods for inguinal hernia surgeries - (:unkn) unknown (Anestezi Dergisi, 2017)
Objective: This randomized prospective study aimed to compare the quality of two anesthetic techniques, patient comfort, and perioperative complications of spinal versus epidural anesthesia for inguinal hernia repair. Method: Seventy-five consented patients undergoing elective inguinal hernia repair were randomized into: spinal anesthesia group (SA group, n=37) and epidural anesthesia group (EA group, n=38). Patients in each group were compared for intraoperative hypotension, time of onset of anesthesia, duration of surgery, intravenous fluid consumption, postoperative pain, first pain sensation time (FPT), perioperative complications and hospital length of stay. Results: The SA group had significantly shorter mean time of onset for anesthesia (5.08 vs 11.47 min) than the EA group (p<0.0001). Visual analogue scale (VAS) scores at the postoperative 12th (2.7±1.9 vs 3.6±1.4) and 24th (0.6±0.9 vs 2.2±1.9) hours of the SA group were significantly lower than EA group (p=0.028, p=0.0001, respectively). FPT, the hospital length of stay, duration of surgery and intravenous fluid consumption were comparable between the two groups. Conclusion: Spinal block application was found to be superior to epidural block due to its advantages of early onset of anesthesia and a better postoperative pain control.
Keywords: Epidural anesthesia; Inguinal hernia; Spinal anesthesia